The effect of muscle type and ageing on Near Infrared (NIR) Spectroscopy classification of game meat species using a portable instrument - Dumalisile, Pholisa (Stellenbosch : Stellenbosch University, 2021)
Thesis (PhDFoodSc)--Stellenbosch University, 2021.